Development of Android-Based Interactive Multimedia on SPLDV Material for Mathematics Learning Evaluation Instruments - Nasution, Dewi Angraini (EDUCTUM: Journal Research, 2023)
Android-based interactive multimedia has now become a trend in improving user experience. Android-based interactive multimedia is an operating system that supports learning programs, which has the characteristic of encouraging students to be able to study independently without having to be guided. The development of Android-based interactive multimedia can provide significant benefits in various fields, such as education, entertainment and business. The development of Android-based interactive multimedia on SPLDV material can increase students' understanding through visualization and interactivity. Such multimedia may include animations, simulations, and interactive exercises to reinforce SPLDV concepts. The aim of this research is to develop Android-based interactive multimedia as an evaluation instrument for mathematics learning with a focus on SPLDV material. The research method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Evaluation instruments are designed to enhance students' understanding of the concept of SPLDV through an interactive multimedia approach.